Cascadable Current-Mode First-Order and Second-Order Multifunction Filters Employing Grounded Capacitors - Jiun-Wei Horng; Chun-Li Hou; Ching-Yao Tseng; Ryan Chang; Dun-Yih Yang (Active and Passive Electronic Components)
A configuration for realizing low input and high output impedances current-mode multifunction filters using multiple output second-generation current conveyors (MOCCIIs) is presented. From the proposed circuit configuration, first-order allpass, highpass, lowpass and second-order allpass, notch, bandpass filters can be obtained. The simulation results confirm the theoretical analysis.